PELATIHAN ENTREPRENEUR MUDA MELALUI DIGITAL MARKETING DAN ENGLISH FOR BUSINESS BAGI GENERASI MUDA NAHDLATUL ULAMA - Ade Christanty Yudha Bestari; Dinar Faiza; Adityo Nugroho; Meilina Haris Mayekti (Migunani Nusantara: Jurnal Pengabdian Kepada Masyarakat, 2026)
The development of the digital economy requires young people to possess entrepreneurial competencies supported by digital marketing and international communication skills. However, members of IPNU and IPPNU Kalibangkang, Ayah District, Kebumen Regency, still face limitations in business development and English proficiency related to business activities. This community service program aimed to improve young entrepreneurs’ competencies through digital marketing training and the implementation of English for Business. The program was conducted through several stages, including coordination, needs assessment, socialization, training, practice, and evaluation. The activities were carried out using hybrid and online approaches involving members of IPNU and IPPNU as participants. The results indicated an improvement in participants’ understanding of entrepreneurship concepts, digital marketing strategies, the use of social media for promotion, and the application of English vocabulary and expressions in business contexts. Furthermore, the program increased participants’ motivation to develop digital-based businesses independently. This community service activity contributed to strengthening the capacity of rural youth in facing the challenges of the digital economy and globalization.